Global estimates of viral suppression in children and adolescents and adults on antiretroviral therapy adjusted for missing viral load measurements: a multiregional, retrospective cohort study in 31 countries. Issue 12 (December 2021) - Han, Win Min; Law, Matthew G; Egger, Matthias; Wools-Kaloustian, Kara; Moore, Richard; McGowan, Catherine; Kumarasamy, Nagalingesawaran; Desmonde, Sophie; Edmonds, Andrew; Davies, Mary-Ann; Yiannoutsos, Constantin; Althoff, Keri N; et al.
Summary: Background: As countries move towards the UNAIDS's 95-95-95 targets and with strong evidence that undetectable equals untransmittable, it is increasingly important to assess whether those with HIV who are receiving antiretroviral therapy (ART) achieve viral suppression. We estimated the proportions of children and adolescents and adults with viral suppression at 1, 2, and 3 years after initiating ART. Methods: In this retrospective cohort study, seven regional cohorts from the International epidemiology Databases to Evaluate AIDS (IeDEA) consortium contributed data from individuals initiating ART between Jan 1, 2010, and Dec 31, 2019, at 148 sites in 31 countries with annual viral load monitoring. Only people with HIV who started ART after the time a site started routine viral load monitoring were included. Data up to March 31, 2020, were analysed. We estimated the proportions of children and adolescents (aged <18 years at ART initiation) and adults (aged ≥18 years at ART initiation) with viral suppression (viral load <1000 copies per mL) at 1, 2, and 3 years after ART initiation using an intention-to-treat approach and an adjusted approach that accounted for missing viral load measurements. Findings: 21 594 children and adolescents (11 812 [55%] female, 9782 [45%] male) from 106 sites in 22 countries and 255 662 adults (163 831 [64%] female, 91 831 [36%] male) from 143 sites in 30 countries were included. Using the intention-to-treat approach, the proportion of children and adolescents with viral suppression was 7303 (36%) of 20 478 at 1 year, 5709 (30%) of 19 135 at 2 years, and 4287 (24%) of 17 589 at 3 years after ART initiation; the proportion of adults with viral suppression was 106 541 (44%) of 240 600 at 1 year, 79 141 (36%) of 220 925 at 2 years, and 57 970 (29%) of 201 124 at 3 years after ART initiation. After adjusting for missing viral load measurements among those who transferred, were lost to follow-up, or who were in follow-up without viral load testing, the proportion of children and adolescents with viral suppression was 12 048 (64% [plausible range 43–81]) of 18 835 at 1 year, 10 796 (62% [41–77]) of 17 553 at 2 years, and 9177 (59% [38–91]) of 15 667 at 3 years after ART initiation; the proportion of adults with viral suppression was 176 964 (79% [53–80]) of 225 418 at 1 year, 145 552 (72% [48–79]) of 201 238 at 2 years, and 115 260 (65% [43–69]) of 178 458 at 3 years after ART initiation. Interpretation: Although adults with HIV are approaching the global target of 95% viral suppression, progress among children and adolescents is much slower. Substantial efforts are still needed to reach the viral suppression target for children and adolescents. Funding: US National Institutes of Health.